2015
DOI: 10.4251/wjgo.v7.i11.317
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of MET in gastric cancer

Abstract: for patients with metastatic or unresectable gastric cancer (GC), although outcomes remain unfavorable. Many molecular-targeted therapies inhibiting signaling pathways of various tyrosine kinase receptors have been developed, and monoclonal antibodies targeting human epidermal growth factor receptor 2 or vascular endothelial growth factor receptor 2 have become standard therapy for GC. Hepatocyte growth factor and its receptor, c-MET (MET), play key roles in tumor growth through activated signaling pathways fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 76 publications
0
25
0
1
Order By: Relevance
“…Moreover, FGFR2 amplification was mutually exclusive from the amplification of other RTKs [4]. The overexpression of HER2 or c-MET was observed more frequently in IGC than in DGC [6, 24], suggesting that a signaling pathway activated by these RTKs might have a critical role in the progression and prognosis of IGC. HER2 overexpression was often found in IGC without significant association of FGFRs in this study, and our results might support those of another study reporting exclusive RTK expression [5].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FGFR2 amplification was mutually exclusive from the amplification of other RTKs [4]. The overexpression of HER2 or c-MET was observed more frequently in IGC than in DGC [6, 24], suggesting that a signaling pathway activated by these RTKs might have a critical role in the progression and prognosis of IGC. HER2 overexpression was often found in IGC without significant association of FGFRs in this study, and our results might support those of another study reporting exclusive RTK expression [5].…”
Section: Discussionmentioning
confidence: 99%
“…As for the two other gastric cancer cell strains, N87 and SGC7901 cells had elevated ANGPTL2 protein expression levels that were slightly lower compared to normal levels. The probable explanation is that the N87 and SGC7901 cell lines had a lower metastatic capacity and the BGC823 and PAMC82 cell lines had a higher degree of malignancy, which exhibited strong migratory ability[32-34]. Recent studies have reported that the carcinogenic capacity of PAMC82 cells is higher than that of N87 cells[35,36].…”
Section: Discussionmentioning
confidence: 99%
“…As another important member of RTK family, c-Met has similar molecular structure and is overexpressed in gastric cancer cells [37, 38]. Therefore, we hypothesized that PKG II may exert a similar inhibitory on the activation of c-Met.…”
Section: Discussionmentioning
confidence: 99%